1997
DOI: 10.1002/adma.19970091206
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented thermo‐ and ion‐responsive behavior of a non‐ionic water‐soluble polysilane

Abstract: Communications negative ion mode. methane): ' H NMR (300 MHz, CDC13): 6 = 4.38 (s, ZH), 7.18-7.95 (m, 28H): I3C NMR (250 MHz, CDCI,): 6 = : Elemental analysis calc. for C46H3"OZ (614.49): C 89.90, H 4.88; found: C 90.02, H 4.76.Thermogravimefric (TG) and Differential Scanning Calorimetric (DSC) Studies: Simultaneous TG-DSC measurements were performed using a TG-DSC 111 (SETARAM, France). The inclusion reaction of acetone from the gas phase was studied in isothermal mode at 25 "C. Inclusion was initiated by sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 18 publications
(2 reference statements)
1
26
0
Order By: Relevance
“…strong solute-solvent interactions exist. Hence, in aqueous solution, 7 adopts an even more condensed random coil conformation with the polar oligo(oxyethylene) side chains extending into the water phase and the Si-CH 3 and Si-C 3 H 6 -groups positioned at the center of the coil, preserving the apoiar character of the backbone ('unimolecular micelle' analogue) (3,28). Thus, at room temperature, solvent polarity dictates the backbone structure of 7.…”
Section: Thermoresponsive Behavior Of Polysilanesmentioning
confidence: 97%
See 1 more Smart Citation
“…strong solute-solvent interactions exist. Hence, in aqueous solution, 7 adopts an even more condensed random coil conformation with the polar oligo(oxyethylene) side chains extending into the water phase and the Si-CH 3 and Si-C 3 H 6 -groups positioned at the center of the coil, preserving the apoiar character of the backbone ('unimolecular micelle' analogue) (3,28). Thus, at room temperature, solvent polarity dictates the backbone structure of 7.…”
Section: Thermoresponsive Behavior Of Polysilanesmentioning
confidence: 97%
“…electroluminescence, microlithography, thermo-, piezo-, solvato-and surfacemediated chromism as well as thermoresponsive behavior (1,3). Introducing branching points in the silicon backbone branched polysilanes, viz.…”
mentioning
confidence: 99%
“…Apparently, the introduction of the dimethylsilane units does not influence the silicon backbone conformation, i. e. the dimethylsilane sequences do not introduce a higher degree of order in the backbone. [3,6] This is attributed to the occurrence of a slow single-chain transition from a disordered to a more ordered backbone conformation. 340 nm.…”
Section: Temperature Dependent Uv-absorption Characteristics Of 4 Namentioning
confidence: 99%
“…[1][2][3][4] They exhibit improved solubility properties and exhibit improved wettability for inorganic substrates in comparison to common alkyl and aryl functionalized polysilanes. [6] Another feature of polysilanes with ether sequences in their side chains is their ability to complex metal cations. Previously, we have reported that aqueous solutions of these polysilanes possess thermoresponsive properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation